Odpowiedź :
Odpowiedź: jak niżej
Szczegółowe wyjaśnienie:
Z4.
2x + 3 = 15 / -3
2x = 12 / :2
x = 6
5x + 13 = 23 / -13
5x = 10
x = 2
Z5.
2(x + 3) = 10 / :2
x + 3 = 5
x = 2
3(x - 1) + 2 = 8 / -2
3(x - 1) = 6 / :3
x - 1 = 2 / + 1
x = 3
Z6.
2(3x - 4) = 10x
6x - 8 = 10x / - 10x
-4x - 8 = 0 / + 8
-4x = 8
4x = -8
x = -2
-4x = 3(6 - 2x)
-4x = 18 - 6x / + 6x
2x = 18
x = 9
Z7.
3(x + 3) = 2(x + 4) + x + 1
3x + 9 = 2x + 8 + x + 1
3x + 9 = 3x + 9
0 = 0
x ∈ R (tożsamość)
2x - 4 - 3(2 - x) = 5(2x - 1)
2x - 4 - 6 + 3x = 10x - 5
5x - 10 = 10x - 5 / +5
5x - 5 = 10x / -5x
-5 = 5x
x = -1